Ubarampe Ritual 'Guyang Jaran' in the Jaran Kepang Turonggo Mudo Art in Temanggung: A Semiotic Study by Charles Sanders Peirce - Fitrotul Arofah; Sunarya Sunarya; Nuning Zaidah (Jurnal Indonesia Sosial Sains, 2024)
Jaran Kepang dance is a Javanese art form that features horses made of woven bamboo. This dance is not only entertainment for the community, but also holds values that symbolize life in Javanese society. This research aims to reveal the meaning of ubarampe in the guyang jaran ritual performed in the art of jaran kepang. This research used a descriptive qualitative method with Charles Sanders Pierce's semiotic theory. The research involved the Jaran Kepang Turonggo Mudo group in Legoksari Village, Tlogomulyo District, Temanggung Regency. Data were collected through interviews, observations, and documentation, then analyzed using data source triangulation. The results showed that, the guyang jaran ritual means bathing horses in the sendhang which starts from installing offerings to end praying together at pepundhen as a form of respect for ancestral spirits, repelling bad luck, and preserving culture. Some types of ubarampe used are tumpeng, sega kapirata, sega bakar, endhog jawa, ingkung, cambah pethek, juaddah pasar, jenang abang putih, incense, candles, cigarettes, kembang setaman, kembang durang, kembang wangi, degan ijo, and wedang 7 werna. Overall, the ubarampe in the guyang jaran ritual has the meaning of prayer requests, gratitude, and a form of harmonious relationship between humans and nature as well as a medium for the Legoksari village community and makes it integral in cultural and spiritual practices.